2021
DOI: 10.1002/qua.26770
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of double transition metal (Cr1−xZrx)2AlC MAX phases as thermal barrier coatings: Insight from density functional theory

Abstract: Herein, a high purity (Cr 1Àx Zr x ) 2 AlC solid solutions (with x = 0-1) have been investigated intensively using the first principles density functional theory calculations. The optimized structural parameters were founded to be in good agreement with the experimental results, and increased steadily with rising Zr in (Cr 1Àx Zr x ) 2 AlC solid solutions. The elastic constants C ij and enthalpy formation have been calculated and firmly confirmed that these solid solutions were mechanically and thermodynamical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Furthermore, the ground-state physical properties of Pb(Mg 1/ 3 Nb 2/3 )O 3 compounds are predicted to be the most tolerant material for thermal barrier coating. 19 Numerous studies reported the halides and oxides perovskites and MAX phase which possesses the physical, mechanical, and chemical properties because of the potential applications in various elds, [4][5][6][7][20][21][22] and it is observed that our investigated results, show consistency with the available results in the literature. So, this class of materials perovskite oxides promising applications for enlightening properties for various technologically equipped societies.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the ground-state physical properties of Pb(Mg 1/ 3 Nb 2/3 )O 3 compounds are predicted to be the most tolerant material for thermal barrier coating. 19 Numerous studies reported the halides and oxides perovskites and MAX phase which possesses the physical, mechanical, and chemical properties because of the potential applications in various elds, [4][5][6][7][20][21][22] and it is observed that our investigated results, show consistency with the available results in the literature. So, this class of materials perovskite oxides promising applications for enlightening properties for various technologically equipped societies.…”
Section: Introductionsupporting
confidence: 89%
“…For both YTiO 3 and YFeO 3 compounds the T m (melting temperature) is calculated using the following expression. 18,19,21,22,48…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…In the above equations, v m is the average sound velocity which is calculated from longitudinal (v l ) and transverse (v t ) sound velocities, respectively, r is the mass density, N A is Avogadro's number, M is the molar mass, n is the number of atoms in the unit cell, K B is the Boltzmann's constant and h is the Planck's constant. The calculated Debye temperature is 627 K which is relatable with other promising compounds [95,96]. Table 6 illustrates that the Θ D value of the compound under study is less than that of the Ti 2 PB 2 compound, possibly because of the lower stiffness constant of Mo 4 Y 2 Al 3 B 6 compared to Ti 2 PB 2 (refer to table 2).…”
Section: Thermodynamic Propertiesmentioning
confidence: 85%